IMF exchange rate policy advice. - Takagi, Shinji, 1953-; Hicklin, John, 1953-; International Monetary Fund. Independent Evaluation Office ([Washington, D.C.] : Independent Evaluation Office of the International Monetary Fund, 2007)
This is a report on exchange surveillance which lies at the core of the IMF's responsibilities. The report argues that a revalidation of the fundamental purpose of surveillance is warranted while no direct connection was made between the shortcomings noted in this report and other review decsions
"This report was prepared by an IEO team headed by Shinji Takagi and John Hicklin"--P. x.
Includes bibliographical references.
opc 25/02/15
Loans
Keywords: International Monetary Fund -- Evaluation; Foreign exchange rates